Gastric Cardiac Cancer (Springer International Publishing, 2018)
This book is designed to present readers with comprehensive, high-quality research results on almost all aspects of this carcinoma in clinical management, from correct determination of the esophagogastric junction, issues on cardiac mucosa, epidemiology, and natural history, to clinical, endoscopic, and histopathologic features and diagnostic pitfalls of this carcinoma at both early and advanced stages. Once diagnosed and correctly staged, clinical management of this carcinoma at the early stage is addressed primarily with endoscopic therapy employing the latest endoscopic technology such as endoscopic submucosal dissection, in which detailed technical topics of the endoscopic therapy are written by experts in the field with sections from pre-resection staging and patient preparation to post-resection complications and management. Subsequently, clinical management of gastric cardiac carcinoma at advanced stages is discussed at length with a personalized, multidiscipline approach with strategies from surgical resections with various methods, to pre-, peri- and post-resection chemoradiation therapies as well as the most advanced immunotherapy. A state-of-art approach with the results of meta-analyses and large-scale randomized double-blinded clinical trials are employed throughout these chapters. For patients at the terminal ill stage, the appropriate palliative care plan is presented by experienced clinicians armed with the latest clinical practice guidelines to better manage and help those patients in the last period of their lives.